2017
DOI: 10.1080/02713683.2017.1362003
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Cytokine Analysis of Aqueous Humor from the Patients with Chronic Primary Angle Closure Glaucoma

Abstract: These results suggest that the aqueous cytokine levels of chronic PACG eyes differ significantly from nonglaucomatous eyes. This is the first study reporting significantly increased levels of eotaxin, MIP-1β, and IP-10 and lower levels of TNF-α, IL-5, IL-9, IL-17, and GM-CSF in chronic PACG patients, suggesting a plausible role of these inflammatory cytokines in its pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…10,11,18 However, in line with studies performed by others, 10,19 our results did not show any statistically significant difference in terms of AH Aβ 42 concentration between the glaucoma and control groups or with respect to other clinical parameters. Conversely, we found a significant increase of TP in the AH of glaucomatous patients, consistent with previous reports showing an increment of proinflammatory cytokine [20][21][22][23] and proteins related to the extracellular matrix remodeling 24 in the AH of subjects affected by glaucoma. Interestingly, our results indicate that this increase in TP was greater within the female group of glaucomatous patients, although the lower number of male patients could have biased these results (12 male vs. 20 female glaucomatous AH samples).…”
Section: Discussionsupporting
confidence: 92%
“…10,11,18 However, in line with studies performed by others, 10,19 our results did not show any statistically significant difference in terms of AH Aβ 42 concentration between the glaucoma and control groups or with respect to other clinical parameters. Conversely, we found a significant increase of TP in the AH of glaucomatous patients, consistent with previous reports showing an increment of proinflammatory cytokine [20][21][22][23] and proteins related to the extracellular matrix remodeling 24 in the AH of subjects affected by glaucoma. Interestingly, our results indicate that this increase in TP was greater within the female group of glaucomatous patients, although the lower number of male patients could have biased these results (12 male vs. 20 female glaucomatous AH samples).…”
Section: Discussionsupporting
confidence: 92%
“…Next, we compared our data to data acquired from the analysis of human AH removed during cataract surgery by Sharma et al, POAG and cataract samples by Duvesh et al and control and PEX samples by Garweg et al (Table S3) [24,41,42]. We found that the level of bFGF, G-CSF, IL-1Ra, IL-6 and RANTES was higher in our samples; the level of IL8, MIP1a, MIP1b and eotaxin was higher in the study carried out by Sharma et.…”
Section: The Analysis Of Aqueous Humourmentioning
confidence: 99%
“…In humans with cataracts, Wang et al (2016) used ELISA to quantify the concentration IL-1β in the aqueous humor and reported concentrations that ranged from 14.9 to 19.4pg/mL; which were higher than the ones reported here for mature (6.00) and hypermature (6.03pg/mL) cataracts. In another studies that were also conducted in humans with cataracts in which multiplex bead immunoassay was used to quantify IL-1 β, much lower values of this cytokine were reported (0.002 to 1.0pg/mL) (Takay et al 2012, Duvesh et al 2017. Quantification of IL-1 β in the aqueous humor of cataractous human eyes assessed by cytometric bead array revealed concentrations that ranged from 2.7±0.0 to 5.29±0.9pg/mL (Aketa et al 2017, Duvesh et al 2017; which were closer to our results.…”
Section: Discussionmentioning
confidence: 99%
“…In another studies that were also conducted in humans with cataracts in which multiplex bead immunoassay was used to quantify IL-1 β, much lower values of this cytokine were reported (0.002 to 1.0pg/mL) (Takay et al 2012, Duvesh et al 2017. Quantification of IL-1 β in the aqueous humor of cataractous human eyes assessed by cytometric bead array revealed concentrations that ranged from 2.7±0.0 to 5.29±0.9pg/mL (Aketa et al 2017, Duvesh et al 2017; which were closer to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation